Multiple output selection-LAS algorithm in large MIMO systems - Li, Peng; Murch, Ross D. (IEEE communications letters, 2010)
We present a low-complexity algorithm for detection in large MIMO systems based on the likelihood ascent search (LAS) algorithm. The key idea in our work is to generate multiple possible solutions or outputs from which we select the best one. We propose two possible approaches to achieve this goal and both are investigated. Computer simulations demonstrate that the proposed algorithm, Multiple Output Selection-LAS, which has the same complexity order as that of conventional LAS algorithms, is superior in bit error rate (BER) performance to LAS conventional algorithms. For example, with 20 antennas at both the transmitter and receiver, the proposed MOS-LAS algorithm needs about 4 dB less SNR to achieve a target BER of 10 -4 for 4-QAM.